APPLICATION OF OZONE TECHNOLOGIES IN CROP CULTIVATION - SHCHERBATIUK, TETIANA; ANDREYEVA, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The agro-industrial complex is one of the most developing spheres of the economy. Growing needs for food, new ways of tilling fields, storing seeds and finished agricultural products lead to the emergence of technological industries, the success of which is largely determined by a combination of classical standardized approaches and innovative search methods. Often the sources of new methods are found in areas of knowledge or areas of practical application of parallel scientific disciplines. Wide and pervasive use of ozone technologies in general ozone therapy and also in particular preventive and clinical medicine for a hundred years has become one of the key markers of interest in the use of ozone in various spheres of the economy, including in the agro-industrial complex. The paper shows a brief overview of works published in the last three years in peer-reviewed editions, devoted to the results of the use of ozone in crop production. Three areas of use of this reagent are analyzed: first of all, reducing the concentration of fungicide, increasing the growth and quality of vegetable crops using fertigation; secondly, preserving the freshness of fruits, berries and vegetables; thirdly, processing of grain raw materials during drying with an ozone-air mixture. Despite certain successes in the use of ozone in the agro-industrial field, the mechanisms at the level of genetic, biochemical and physiological processes of plants remain poorly understood, and it is this knowledge that will make it possible to regulate plant metabolism and develop standardized regimes for the use of ozone technologies in crop production. Taking into account the expected synergy between agronomic science and post-genomic technologies, it is possible to predict qualitatively new explanations for the action of ozone through the mechanisms of regulation of the soil and plant microbiome. Ukrainian manufacturers of ozone generators, agrarian scientists and agro-industrialists have every reason to unite to significantly raise the scientific and practical level of applying ozone technologies in agriculture. Now is the time for transformation, modernization, and therefore a hopeful future.
Keywords: ozone; ozone technologies; crop production; fertilization; storage of fruits; berries and vegetables; drying of grain raw materials